Treated Olive Cake as a Non-forage Fiber Source for Growing Awassi Lambs: Effects on Nutrient Intake, Rumen and Urine pH, Performance, and Carcass Yield - M. S. Awawdeh; B. S. Obeidat (Asian-Australasian Journal of Animal Sciences, 2013)
The objective of this study was to investigate the effects of partial replacement of wheat hay with sun-dried (SOC) or acid-treated SOC (ASOC) olive cake on nutrient intake and performance of Awassi lambs. An additional objective was to study the effects of acid treatment of olive cake (OC) on its chemical composition and nutritive value. On DM basis, sun-drying of OC did not dramatically affect its chemical composition. On the other hand, treating SOC with phosphoric acid decreased (p<0.05) SOC contents of neutral detergent fiber. Twenty seven male lambs (17.6±0.75 kg body weight) individually housed in shaded pens were randomly assigned to one of three dietary treatments (9 lambs/treatment). Dietary treatments were formulated to be isocaloric and isonitrogenous by replacing 50% of wheat hay in the control diet (CTL) with SOC or ASOC and to meet all nutrient requirements. Dietary treatments had no effects on nutrient intake or digestibility except for ether extract. Lambs fed the SOC diet had (p = 0.05) faster growth rate, greater final body weight, and greater total body weight gain in comparison with the CTL diet, but not different from the ASOC diet. Additionally, lambs fed the SOC diet had greater (p = 0.03) hot and cold carcass weights than the ASOC diet, but not different from the CTL diet. However, feed conversion ratios and dressing percentages were similar among dietary treatments. In conclusion, replacing half of dietary wheat hay with SOC improved performance of Awassi lambs with no detrimental effects on nutrients intake or digestibility. No further improvements in the nutritive value of SOC and lambs performance were detected when SOC was treated with acid.